2020
DOI: 10.1088/1742-6596/1554/1/012067
|View full text |Cite
|
Sign up to set email alerts
|

An initial observation of learning devices and mathematical problem solving ability of senior high school students

Abstract: A good learning devices will deliver students to have good mathematical problem solving skills. This type of research was a descriptive research by qualitative approach. The initial observation was aimed at finding out, reviewing and explaining problem-solving ability of high school students in mathematics learning and condition of learning devices used and developed by teachers, then whether it was necessary to continue research development based on realistic mathematics education to improve the mathematical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Figure 1 shows a detailed explanation of each problem-solving step as suggested by Polya. In addressing problem solving in teaching and learning, some researchers focused on the teacher (Csíkos & Szitányi, 2020;Ozdemir & Seker, 2021;Tambunan, 2019), while others focused on different aspects of learners (Amalia et al, 2017;Fitriani & Arnawa, 2020;Kholid et al, 2021;LaForce et al, 2017;Lubienski et al, 2021).…”
Section: Problem Solving Approach In Mathematics Teaching and Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows a detailed explanation of each problem-solving step as suggested by Polya. In addressing problem solving in teaching and learning, some researchers focused on the teacher (Csíkos & Szitányi, 2020;Ozdemir & Seker, 2021;Tambunan, 2019), while others focused on different aspects of learners (Amalia et al, 2017;Fitriani & Arnawa, 2020;Kholid et al, 2021;LaForce et al, 2017;Lubienski et al, 2021).…”
Section: Problem Solving Approach In Mathematics Teaching and Learningmentioning
confidence: 99%
“…The use of teaching models has been found to enhance high order problem-solving skills among students and overall mathematical cognitive development (Son, 2020). Alongside these models, teachers can also develop learning devices for students to enhance their problemsolving abilities (Fitriani & Arnawa, 2020), as this can help them in their learning. However, in their study, Fitriani and Arnawa (2020) found that learning devices that had been developed for students were too general and did not facilitate the link to real-life problems, thereby making mathematics instruction meaningless.…”
Section: Problem Solving Approach In Mathematics Teaching and Learningmentioning
confidence: 99%
“…Learning devices will facilitate the learning process in achieving learning objectives. Learning devices can be in the form of information presented in various types of media that can assist students in improving the learning outcomes to be achieved (Sudarsana et al, 2019;Lukito, 2019;Fitriani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%